Security of Adhoc Networks Against Routing Protocols Attacks - Benazzi, Moussaab; Supervised: Benouis, Mohamed (University of M'sila, 2015)
Now-a-days, wireless ad hoc networks (MANETs) are playing vital role for facilitating communication between different entities for different purposes. In case of wireless ad hoc networks security aspect has now becomes a very major concern and most of the current researches are focusing in the same direction ,However, Due to security vulnerabilities of the routing protocols, wireless ad hoc networks may be unprotected against attacks by the malicious nodes. One of these attocks is the Black Hole Attack which I have made my study on it.
Keywords: MANET / routing protocols security / black hole.